Sustainable Marketing Practices Within The Agricultural Sector And Their Reality In Algeria - A Standard Study (1960-2020) - Saker, Bilal (جامعة الوادي - University of Eloued, 2022)
The study aims to show the nature of sustainable marketing practices within the agricultural sector in Algeria, through a standard study based on annual data for the period from 1965 to 2020, depending on a number of variables, and the method for that is a time series with the use of reference points The study found differences in the outputs of marketing practices in the time periods under study within the agricultural sector, while highlighting its contribution to national returns.
مقال
Keywords: Sustainable marketing practices ; Agricultural marketing ; Time series ; Algeria